Conservation Biogeography of Tenebrionid Beetles: Insights from Italian Reserves - Simone Fattorini (Diversity, 2020)
The species-area relationship (SAR), the latitudinal gradient, the peninsula effect, and the elevational gradient are widespread biogeographical patterns. Using data from Italian reserves, these patterns were tested for tenebrionids and used as a framework to calculate expected extinction rates following area loss. Area was an important determinant of overall tenebrionid species richness, but not for xylophilous and endemic species. Thus, focusing on reserve areas is not the best approach for conserving insects with specialised ecology and restricted distribution. In general, species richness declined northwards, which contrasts with the peninsula effect, but conforms to the European latitudinal pattern observed in most taxa because of current and past biogeographical factors. Minimum elevation had an overall negative influence, as most tenebrionids are thermophilic. However, xylophilous tenebrionids, which are mainly associated with mesophilic forests, did not decline northwards, and were positively influenced by higher elevational ranges that allow more forms of vegetation. SAR-based extinction rates reflect species dispersal capabilities, being highest for geophilous species (which are mainly flightless), and lower for the xylophilous species. Extinction rates based on multiple models indicate that the use of area alone may overestimate extinction rates, when other factors exert an important role in determining species richness.